2021
DOI: 10.3389/fmars.2021.643302
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Spatiotemporal Scales to Aggregate Satellite Ocean Color Data for Nearshore Reefs and Tropical Coastal Waters: Two Case Studies

Abstract: Remotely sensed ocean color data are useful for monitoring water quality in coastal environments. However, moderate resolution (hundreds of meters to a few kilometers) satellite data are underutilized in these environments because of frequent data gaps from cloud cover and algorithm complexities in shallow waters. Aggregating satellite data over larger space and time scales is a common method to reduce data gaps and generate a more complete time series, but potentially smooths out the small-scale, episodic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…We foresee a similar issue for water quality metrics: Although we expect that the seasonal climatology and associated variability metric used in these models are fairly robust in the long term, the current models do not capture acute events caused by intense rainfall and associated runoff, which are known to influence disease (Haapkylä et al, 2011). Although we attempted to measure acute events with ocean color data (procedure described in Geiger et al, 2021), we found that the available data were too sparse to use in the models, with no satellite coverage for ~80% of the corresponding survey data. More importantly, the ocean color data unavailable during events were not random but aggregated during cloudy days; in other words, days that are most likely associated with rain events that can increase disease risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We foresee a similar issue for water quality metrics: Although we expect that the seasonal climatology and associated variability metric used in these models are fairly robust in the long term, the current models do not capture acute events caused by intense rainfall and associated runoff, which are known to influence disease (Haapkylä et al, 2011). Although we attempted to measure acute events with ocean color data (procedure described in Geiger et al, 2021), we found that the available data were too sparse to use in the models, with no satellite coverage for ~80% of the corresponding survey data. More importantly, the ocean color data unavailable during events were not random but aggregated during cloudy days; in other words, days that are most likely associated with rain events that can increase disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…We used the mean (i.e., climatology) and associated variability in Kd(490) to represent seasonal changes because, to date, these values are too highly variable and too infrequently available in the coastal zone to use actual, or even 3-week composite, values. Additional details on the derivation of these metrics and their accuracy can be found in Geiger et al (2021). We include month in the model as a proxy for all other seasonally changing conditions.…”
Section: Seasonally Changing Datamentioning
confidence: 99%
“…We foresee a similar issue for water quality metrics: while we expect that the seasonal climatology and associated variability metric used in these models are fairly robust in the long-term, the current models do not capture acute events caused by intense rainfall and associated runoff, which are known to influence disease (Haapkylä et al, 2011). Although we attempted to measure acute events with ocean color data (procedure described in Geiger et al, 2021), we found that the available data were too sparse to use in the models, with no satellite coverage for ∼80% of the corresponding survey data. More importantly, the ocean color data unavailable during events were not random, but aggregated during cloudy days; in other words, days that are most likely associated with rain events that can increase disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…To characterize chronic water quality conditions in both model development and forecasting, we aggregated the diffuse attenuation coefficient at 490 nm, Kd(490), as a proxy for turbidity from VIIRS data (Kirk, 1994). We calculated long-term Kd(490) median and variability for each reef pixel by overlaying aggregated data from 2012-2020 (i.e., all data available at the time of study) within a 5-pixel buffer (750 m becomes ∼8.25 km resolution) following methods from Geiger et al, 2021 to increase data availability, as nearshore ocean color data are notoriously patchy. These metrics are indicative of spatial differences in water quality across reefs, providing information on locations that have chronically good or poor water quality and those that are exposed to a large range of water quality conditions throughout the year versus those with more consistent conditions.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation